Pengaruh Reward dan Punishment Terhadap Disiplin Waktu Kerja Karyawan pada CV Berkah Sukses Berjaya - Hani Rosmawati; Natal Indra (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
In this research, researchers used the Slovin technique, the Slovin technique to calculate and determine samples accurately when conducting research in any field. Based on the results of Reward and Punishment research on work time discipline through simultaneous significant testing (F test), it turns out that there is a significant effect between Reward and employee work time discipline at CV Berkah Sukses Berjaya. It can be concluded that there is a joint influence between Reward and Punishment on employee work time discipline at CV Berkah Sukses Berjaya. The conclusions from the results of the research and discussion above are: 1. Reward Variable (X1) on Emploe Working Time Discipline (Y) seen from the coefficients table, the t value is 2.101, which means t count t table (2,101, 1,697) with a significance of 0.044, 0.05 . So the hypothesis which states that Rewards partially have a positive and significant effect on employee work time discipline can be accepted. 2. So it can be seen that the Punishment variable (X2) on Employee Working Time Discipline (Y) seen from the coefficients table, obtained a t value of 1.552, which means t count t table (1.552, 1.697) with a significance of 0.131, 0.05. So the hypothesis states that partial Punishment has no significant effect on employee work time discipline.